2021
DOI: 10.1016/j.paed.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen therapy in preterm infants: recommendations for practice

Abstract: Oxygen is one of the most commonly used therapies in neonatology but optimum oxygen saturations for preterm infants have been debated for the past 50 years. The history of oxygen use in this population and multiple clinical trials over the years have shown that liberal oxygen administration is associated with retinopathy of prematurity (ROP) and bronchopulmonary dysplasia (BPD) whereas restrictive use results in increased mortality and neurodisability. Pulse oximetry (SpO 2) is a bedside tool to guide the frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 5 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…Another retrospective study by Kumaravel et al revealed that neonates with a birth weight of less than 1,500 grams had higher rates of laser photocoagulation therapy for ROP treatment compared with higher birth weights [ 20 ]. This might be because the lower the birthweight, the more likely it is for a neonate to require oxygenation intervention which is an independent risk factor for the development of ROP [ 21 , 22 ]. Thus, we recommend that oxygenation therapy for preterms should be given with caution, and regular monitoring is advised.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study by Kumaravel et al revealed that neonates with a birth weight of less than 1,500 grams had higher rates of laser photocoagulation therapy for ROP treatment compared with higher birth weights [ 20 ]. This might be because the lower the birthweight, the more likely it is for a neonate to require oxygenation intervention which is an independent risk factor for the development of ROP [ 21 , 22 ]. Thus, we recommend that oxygenation therapy for preterms should be given with caution, and regular monitoring is advised.…”
Section: Discussionmentioning
confidence: 99%
“…As infants who are born prematurely have yet to complete a full-term pregnancy, the respiratory organ and system are often not sufficient to support the respiratory needs of a premature infant. (43) Odds ratio calculation between gestational age and duration of oxygen therapy, as seen in table 4, shows that infants born at ≤ 32 weeks gestation are 2.06 times (95% CI 0.313-13.574) more likely to receive oxygen supplementation for ≥ 7 days. Duration of oxygen supplementation is adjusted to the infant's clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical ventilation and apnea of prematurity, caused by immature respiratory control in preterm neonates, sometimes result in intermittent hypoxic events (Eichenwald et al, 2016; Martin et al, 2011). Oxygen supplementation is an established intervention to counter these periods of hypoxia but increases the risk of exposure to a hyperoxic environment (Ali et al, 2021; Oei & Vento, 2019). Various animal experimental studies, some of which include models of preterm birth, have shown a link between neonatal hyperoxia exposure and changes in cardiac structure and function, resulting in adult heart failure (Bertagnolli et al, 2014; Velten et al, 2011, 2014).…”
Section: The Role Of Maternal and Early Life Environmentmentioning
confidence: 99%